2005
DOI: 10.1177/0899764005275568
|View full text |Cite
|
Sign up to set email alerts
|

Doing Syringe Exchange: Organizational Transformation and Volunteer Commitment

Abstract: The authors examine the organizational transformation of Prevention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…An exception is the study by Kelley, Lune, and Murphy (2005), who analyzed the importance of the phenomenon volunteering for organizational transition. The authors demonstrated the effects of organizational transition (professionalization) on the experience of volunteers and the breakdown of volunteer commitment in an organization called prevention point.…”
Section: President Of a Patient Organizationmentioning
confidence: 95%
“…An exception is the study by Kelley, Lune, and Murphy (2005), who analyzed the importance of the phenomenon volunteering for organizational transition. The authors demonstrated the effects of organizational transition (professionalization) on the experience of volunteers and the breakdown of volunteer commitment in an organization called prevention point.…”
Section: President Of a Patient Organizationmentioning
confidence: 95%
“…The ASB may very well owe its success and longevity to its historical disorganization. Despite success in reaching their immediate goals, members of informal organizations such as ASB seem plagued by their inability to become organized and often worry about the existence of their organization as a reifi cation of their initial intentions (Kelley, Lune, & Murphy, 2005). The isomorphic pressure to formalize is one avenue to legitimacy (Deephouse & Carter, 2005), enabling the introduction of formal structures in the hopes of ensuring organizational survival.…”
Section: The Case For Not Creating a Mission Statement For Asbmentioning
confidence: 99%
“…New volunteers are trained to do specific tasks, not to participate in the organization as a whole. Kelley et al (2005), in their study of an organizational transition from an underground syringe exchange program to a legal, public funded service organization in San Francisco, found that in the new setting, volunteers were mainly doing the unpaid work, while staff made the operational decisions, and volunteers were increasingly left out of information sharing and decision making. The organization more strongly aligned with public institutions and authorities instead of its earlier commitment to the community it was serving.…”
Section: Organizational Transformationsmentioning
confidence: 99%
“…Several studies examine the consequences for volunteering of an organizational transformation from a traditional grassroots association to a more professionalized organization (Kelley et al 2005;Lie and Baines 2007;Warburton and McDonald 2009). This organizational change is mainly caused by a changing policy environment, involving increased public funding, processes of marketization, the emergence of a more competitive environment, a new contract culture and new demands for professionalism.…”
Section: Organizational Transformationsmentioning
confidence: 99%
See 1 more Smart Citation